2013
DOI: 10.2528/pierb13050112
|View full text |Cite
|
Sign up to set email alerts
|

Circular Antenna Array Design by Using Evolutionary Search Algorithms

Abstract: Abstract-Evolutionary Search Algorithms (EA) have been intensively used in solving numerical optimization problems. Since design of antenna arrays is a numerical optimization problem, EAs have been intensively used in solving antenna arrays design problems. Although EAs are widely used in antenna array design problems, a performance comparison study of the intensively used EAs for circular antenna array design problem has been scarcely studied. In this paper, 3 different circular antenna array design problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…In many MOPs, many or even infinite Pareto optimal vectors are distributed in the complete PF. Nevertheless, many multiobjective optimization algorithms are to find a manageable number of Pareto optimal vectors that are evenly distributed along the PF and, thus, are good representatives of the entire PF [1][2][3][4][5][6][7][8][9][10], [24]. Found in the literature, the goal for distributing individuals is that, along with convergence to the Pareto optimal set.…”
Section: Front Uniformly Distributed Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…In many MOPs, many or even infinite Pareto optimal vectors are distributed in the complete PF. Nevertheless, many multiobjective optimization algorithms are to find a manageable number of Pareto optimal vectors that are evenly distributed along the PF and, thus, are good representatives of the entire PF [1][2][3][4][5][6][7][8][9][10], [24]. Found in the literature, the goal for distributing individuals is that, along with convergence to the Pareto optimal set.…”
Section: Front Uniformly Distributed Strategymentioning
confidence: 99%
“…Evolutionary multiobjective optimization methods, such as NSGA-II, differential evolution multiobjective (DEMO), strength-Pareto evolution algorithm (SPEA-2), and multiobjective particle swarm optimization (MOPSO), are provided for the synthesis problem of linear antenna arrays and concentric rings antenna arrays with the objectives of main beam width and SLL [1], [4][5][6][7]. NSGA-II [10] is a popular and efficient multiobjective genetic algorithm, which has been used in several engineering design problems [11][12][13][14], [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The computation and synthesis of current distributions for Dolph-Chebyshev patterns for linear arrays were further developed by others [11][12][13]. The synthesis of a circular array with isotropic elements are documented in [14,15,[23][24][25][26]. Some special cases of directive elements were discussed in [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that, on the whole, BSA outperformed the compared algorithms. BSA was used for circular antenna array design 12 . BSA was used to synthesis concentric circular antenna arrays and linear antenna arrays 13,14 .…”
mentioning
confidence: 99%